CSR and the Job Choices a Preliminary Analysis Among Malaysian Graduates - Syed Taha, Sharifah Thaherah (2008)
Understanding how organizations impact society and potentially benefit a variety of stakeholders is important. The impact that an organization’s corporate social responsibility (CSR) has on graduates can be crucial to organizational survival. This study quantitatively investigates the relationship between CSR and job choices among final year undergraduates business and accounting students. Findings from the study provide evidence that there are several factors that cause graduate to choose a job to the extent on more or less attractive job selection. The study also provide that social policy being part of CSR is less important as compared to ethical policy. For the graduates making career decisions, salary, location and also the ethical policy on the employer seemed to be more important that the presence of other organizational and discretionary behaviour. This research adds to literatures around CSR and employee attractiveness. During the past years, interest in the social responsibility of organization has indeed increased in all sectors and disciplines. Consequently, this study identifies the critical need for future in depth research on job choices and the specific components of CSR.